2017
DOI: 10.1016/j.jpedsurg.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Does thoracoscopy have advantages over open surgery for asymptomatic congenital lung malformations? An analysis of 1626 resections

Abstract: 4 (based on lowest level of article analyzed in meta-analysis/systematic review).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 48 publications
5
39
0
2
Order By: Relevance
“…Against this background, the question arises whether VATS lobectomy leads to measurable advantages in pediatric patients? In the review of the literature, a lower complication rate is found for the minimally invasive procedure than in open surgery (6). The average surgery time was longer in the case of thoracoscopic procedures, while the length of stay in the hospital was shorter (6).…”
mentioning
confidence: 99%
“…Against this background, the question arises whether VATS lobectomy leads to measurable advantages in pediatric patients? In the review of the literature, a lower complication rate is found for the minimally invasive procedure than in open surgery (6). The average surgery time was longer in the case of thoracoscopic procedures, while the length of stay in the hospital was shorter (6).…”
mentioning
confidence: 99%
“…Hence, bleeding control and parenchyma resection can be performed easily without stretching wound or spreading ribs. The complication rates of VATS resection in children differ in the literature, ranging from 4.4% to 30.6% [30,32]. In this study, the VATS complication rate is 38.5% (5/13).…”
Section: Discussionmentioning
confidence: 54%
“…In the recent two decades, thoracoscopic surgery for paediatric patients has become popular worldwide and even has become a routine procedure for congenital lung malformations [2,6,30]. Metaanalysis reports and retrospective comparative studies indicate that VATS is associated with few complications and short hospital stay [4,6,31,32]. Therefore, the procedure has been proven safe and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that thoracoscopic resection is not associated with more risks than open surgery. 10 All of the above-mentioned studies included children from different age groups. As feasibility of pulmonary VATS in neonates and infants up to the age of 12 months has not been investigated systematically, we reviewed the available data in the current literature.…”
Section: Introductionmentioning
confidence: 99%